2020
DOI: 10.1159/000508079
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Endostatin Expression Is Regulated by the pIgA Immune Complex and Associated with Disease Severity of IgA Nephropathy

Abstract: <b><i>Background/Aims:</i></b> Renal vascular injury accounts for the poor outcomes of patients with IgA nephropathy (IgAN). In this study, we investigated whether endostatin, a potent inhibitor of angiogenesis, is associated with IgAN. <b><i>Methods:</i></b> Serum endostatin levels were detected in patients with IgAN, disease controls, and healthy controls, and the correlation among endostatin and clinicopathologic manifestations, as well as prognosis in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Clinical data have reported that damage of endothelium in IgAN with loss of endothelial cells is very common. Dissection of glomerular endothelial cells from the basal membrane, formation of endothelial cavitation, and insertion of the basal membrane was also observed in rat models with IgAN (71,72).…”
Section: Endothelial Cellmentioning
confidence: 86%
See 1 more Smart Citation
“…Clinical data have reported that damage of endothelium in IgAN with loss of endothelial cells is very common. Dissection of glomerular endothelial cells from the basal membrane, formation of endothelial cavitation, and insertion of the basal membrane was also observed in rat models with IgAN (71,72).…”
Section: Endothelial Cellmentioning
confidence: 86%
“…MiR-223 addition could inhibit NF-κB and STAT3 nuclear translocation, thereby alleviating endothelial cell proliferation, ICAM-1 expression, and monocyte adhesion on the endothelium. Another in vitro experiment demonstrated that elevated expression of endostatin, an endogenous angiogenesis inhibitor, and IL-6 with decreased cell proliferation activity was found in cultured endothelial cells after polymeric IgA stimulation ( 72 ). As direct stimulation of IL-6 enhances endothelial cell proliferation, it is reasonable to hypothesize that endostatin secreted by endothelial cells plays a self-protective role in cell proliferation while IL-6 from mesangial cells stimulated by Gd-IgA deposition enhances endothelial cell proliferation, and they collaboratively result in endothelial cell loss and hyperpermeability of endothelium finally.…”
Section: Endothelial Cellmentioning
confidence: 99%
“…It is well known that proteinuria stimulates tubular epithelial cells to release the macrophage chemoattractant protein 1 (MCP-1/CCL2) and cytokines activating macrophages in vitro and in vivo [ 38 , 39 , 40 , 41 ]. In IgAN, MCP1 is highly expressed by tubular epithelial cells [ 20 , 21 ], and is detected in the urine [ 23 , 24 , 26 , 27 ]. Furthermore, its urinary level correlates with tubulointerstitial inflammation, severity of histopathological lesions, and adverse prognosis [ 23 , 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interstitial macrophage infiltration in IgAN kidney biopsies has been associated with poor prognosis and severity of the disease since 2006 [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]; however, this parameter is not included in the Oxford classification. Disease-specific urinary biomarkers can be useful as diagnostic and/or prognostic tools, potentially avoiding second biopsies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of angiogenesis in the glomerular filtration barrier damage in the course of inflammatory diseases such as glomerulonephritis has been demonstrated in different experimental models [ 56 , 57 ]: moreover, a potential role of angiogenesis has been recently described also in human glomerular diseases [ 58 , 59 ]. Several mediators, including Vascular Endothelial Growth Factor (VEGF-A) and nitric oxide (NO) have been shown to play a pivotal role in glomerular capillary repair during inflammatory diseases [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%